Austropuccinia psidii, causing myrtle rust, has a gigabase-sized genome shaped by transposable elements. Issue 3 (27th November 2020) - Tobias, Peri A; Schwessinger, Benjamin; Deng, Cecilia H; Wu, Chen; Dong, Chongmei; Sperschneider, Jana; Jones, Ashley; Lou, Zhenyan; Zhang, Peng; Sandhu, Karanjeet; Smith, Grant R; Tibbits, Josquin; et al.
Abstract : Cultivated strawberry has a compelling domestication history: the earliest cultivars originated in western Europe as spontaneous hybrids between non-sympatric wild species imported from the New World. The origin of those early hybrids went undiscovered for nearly a half century before conscious domestication began. Here, Pincot, Ledda, Feldmann et al . reconstruct the genealogy of cultivated strawberry, illuminating the domestication history and developing a deeper understanding of the interspecific hybrid ancestry and evolutionary forces that shaped phenotypic diversity in the global population. Abstract: Austropuccinia psidii, originating in South America, is a globally invasive fungal plant pathogen that causes rust disease on Myrtaceae. Several biotypes are recognized, with the most widely distributed pandemic biotype spreading throughout the Asia-Pacific and Oceania regions over the last decade. Austropuccinia psidii has a broad host range with more than 480 myrtaceous species. Since first detected in Australia in 2010, the pathogen has caused the near extinction of at least three species and negatively affected commercial production of several Myrtaceae. To enable molecular and evolutionary studies into A. psidii pathogenicity, we assembled a highly contiguous genome for the pandemic biotype. With an estimated haploid genome size of just over 1 Gb (gigabases), it is the largest assembled fungal genome to date. The genome has undergone massive expansion via distinct transposable element (TE) bursts. Over 90% of the genome is covered by TEs predominantly belonging to the Gypsy superfamily. These TE bursts have likely been followed by deamination events of methylated cytosines to silence the repetitive elements. This in turn led to the depletion of CpG sites in TEs and a very low overall GC content of 33.8%. Compared to other Pucciniales, the intergenic distances are increased by an order of magnitude indicating a general insertion of TEs between genes. Overall, we show how TEs shaped the genome evolution of A. psidii and provide a greatly needed resource for strategic approaches to combat disease spread.